The Dysfunctions of Organisational Culture in Enterprise – Research Results - Pietruszka-Ortyl, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article examines the role of organisational culture in building competitive advantage in a knowledge-based organisation. The importance of organisational culture as the main component of intangible resources is highlighted and organisations’ need to study the conditions of dysfunctional organisational culture are emphasised. The article begins with a theoretical synthesis of the literature with a view to describing the dysfunctions and pathologies of organisational culture. The main part analyzes the pathology of organizational culture in the context of its functions and the types and conditions of the knowledge economy. Finally, the theoretical symptoms of emerging dysfunctions are identified, and instruments to be used for the empirical analysis and diagnosis of those dysfunctions are proposed. In this context, the results of pilot comparative empirical research of dysfunctions identified in organisations in Poland are presented. Preliminary research was carried out in 2015 and extended in 2016. The results clearly indicate specific areas of dysfunction. In the opinion of the employees surveyed, the organisational culture they work in offers conditions far from those accepted in a model knowledge-based economy culture – that is, a culture of trust, collaboration and knowledge.